Traditional knowledge of marine resources and its impact on the well-being of coastal communities in Peninsular Malaysia - Salleh, Hayatul Safrah; Mohd Arzaman, Ameer Farhan; Nik Mat, Nik Hazimah; Wan Talaat, Wan Izatul Asma (International Information and Engineering Technology Association, 2023)
Traditional knowledge (TK) concerning the utilization of marine resources has long been employed by coastal communities for their general well-being and income generation. This study aimed to explore the potential of TK related to marine resources for enhancing the well-being of coastal populations in Peninsular Malaysia. A qualitative approach was adopted, with in-depth interviews conducted among 117 participants in the region. Data collection took place during the Movement Control Order (MCO) imposed in Malaysia due to the COVID-19 pandemic, which restricted the ability to conduct face-to-face interviews. The findings of this investigation revealed that TK associated with marine resources plays a crucial role in promoting health among coastal inhabitants. This was assessed by examining the key resources and purposes for which TK was employed within these communities. The present study has the potential to contribute to the development of new knowledge on TK practices, provide valuable information to assist coastal populations in augmenting their income and health, and serve as a reference for governments, agencies, and relevant stakeholders in recognizing the significance of TK. Future research could extend to the Borneo region of Malaysia to obtain diverse perspectives, and a quantitative approach may be employed to achieve a broader generalizability of findings concerning the relationship between TK based on marine resources and societal well-being.